ANALISIS LINGKUNGAN INDUSTRI KERAJINAN BAMBU DI SENTRA INDUSTRI KERAJINAN BAMBU SENDARI KABUPATEN SLEMAN (STUDI KASUS UMKM MEBEL BAMBU LUGUT PRING) - Nisa, Atrina Qoirun; Fatimah, Atika (Ekonis: Jurnal Ekonomi dan Bisnis, 2024)
Abstract: DI Yogyakarta Province has economic advantages in the creative economy sector, especially the crafts subsector. One of the craft subsectors in DI Yogyakarta Province is the Sendari bamboo craft industry center in Sleman Regency. This craft industry which is made from bamboo is quite versatile because it can produce various types of products such as furniture, decorations and household accessories. The uniqueness and beauty of these products provide their own charm so that they are quite popular with local people and foreign tourists. However, the bamboo craft industry has limitations in the number of craftsmen. This was found in the Lugut Pring Bamboo Furniture MSME business which only consists of three employees, namely a father, mother and child who manage the business and are craftsmen. This creates problems with the availability of labor which results in them being less able to develop their business and unable to penetrate the export market like other business actors in the Sendari Bamboo Craft Industry Center. The aim of this research is to analyze the environment of the Lugut Pring Bamboo Furniture MSME industry based on the scope and intensity of competition in the industry, threats from potential competitors, threats from substitute products, buyers' bargaining power and suppliers' bargaining power. The research method used is Porter's Five Forces Model analysis. The research results show that the dimensions of scope and intensity of competition in the industry as well as the threat of substitute products have the highest influence. Meanwhile, the dimensions of buyers' bargaining power, suppliers' bargaining power and threats from potential competitors have a lower influence. Keywords : Bamboo Craft Industry, Porter's Five-Forces Model, Lugut Pring Bamboo Furniture MSMEs.